Naskah Ulu: Obat-Obatan Tradisional Dalam Naskah Kaghas Nomor. Inv 07. 47 Koleksi Museum Negeri Sumatra Selatan (Kajian Filologi) - Muhammad Affan Ridhollah; Nyimas Umi Kalsum; Sholeh Khudin (Tanjak: Sejarah dan Peradaban Islam, 2021)
South Sumatra has known writing traditions from the seventh century to the present, with many artifacts in Sanskrit, ulu, Malay, Javanese, and Latin scripts being found. The ulu script is a script with the ka-ga-nga script that developed and spread in the inland ulu area of ​​south Sumatra. Kaghas manuscript number. INV 07. 47 is one of the manuscripts from the collection of the South Sumatran State Museum, with the Ulu script and Malay dialect, Basemah dialect, which is the area of ​​South Sumatra and made of bark or Kaghas. The problem of this research is how to study the philology of the manuscripts and what medicines are in the text of Kaghas Number. INV 07. 47 collection of the state museum of South Sumatra. The purpose of this research is to edit and find out the contents of the manuscript. The philological method used is the diplomatic edition and the standard edition by describing the manuscript with the original and correcting minor errors that are not clear in the manuscript to be examined. Kaghas manuscript number. INV 07. 47 collection of the state museum of South Sumatra made of bark or brown kaghas with a total of 24 sheets but 13 pages written and still intact. Kaghas manuscript number. INV 07. 47 the collection of the state museum of South Sumatra explains the names of plants and ingredients used as traditional medicines by the local community and also explains how to manage these medicines. This manuscript functions as a medium in conveying the values ​​of local wisdom, telling a story, recording customary law, writing a poem or poem, conveying religious teachings, medicine and treatment, or advice. So it is an important knowledge needed by the community.